2021
DOI: 10.3390/ma14020356
|View full text |Cite
|
Sign up to set email alerts
|

Aluminothermic Reduction of Manganese Oxide from Selected MnO-Containing Slags

Abstract: The aluminothermic reduction process of manganese oxide from different slags by aluminum was investigated using pure Al and two types of industrial Al dross. Two types of MnO-containing slags were used: a synthetic highly pure CaO-MnO slag and an industrial high carbon ferromanganese slag. Mixtures of Al and slag with more Al than the stoichiometry were heated and interacted in an induction furnace up to 1873 K, yielding molten metal and slag products. The characterization of the produced metal and slag phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…The recent published work by the authors showed that the rich Al particles can be recycled via their use for the reduction of manganese oxide from waste from the ferromanganese industry, which yields Al-Mn alloys. 36 In this process, a large portion of the Al in the dross particles is distributed into the produced alloy, and the rest is consumed to reduce manganese oxide (MnO). The non-metallic components are removed via an oxide slag byproduct, without any salt use.…”
Section: Al Recovery From the White Drossmentioning
confidence: 99%
“…The recent published work by the authors showed that the rich Al particles can be recycled via their use for the reduction of manganese oxide from waste from the ferromanganese industry, which yields Al-Mn alloys. 36 In this process, a large portion of the Al in the dross particles is distributed into the produced alloy, and the rest is consumed to reduce manganese oxide (MnO). The non-metallic components are removed via an oxide slag byproduct, without any salt use.…”
Section: Al Recovery From the White Drossmentioning
confidence: 99%
“…Pure aluminum is the Earth's third most abundant element, accounting for about 8% of the mass of the Earth's crust, and it never occurs as a free element in nature [3,4]. At present, aluminum is mainly produced via two different methods: (I) a primary aluminum production from bauxite ore via the Bayer process for alumina extraction, followed by Hall-Heroult electrolysis for Al extraction from alumina, and (II) by recycling aluminum from process scrap and used aluminum products [3][4][5][6][7]. The world's production of aluminum is increasing every year and was approx.…”
Section: Introductionmentioning
confidence: 99%
“…The world's production of aluminum is increasing every year and was approx. 64 million metric tons in 2019 with a daily average of 174.5 thousand tons [3,7], while in 2020 it was over 65 million metric tons in 2020 [8]. As a result of the exposure of liquid aluminum to the oxidizing atmosphere that is present during the process of melting and alloying, a surface oxidation takes place, leading to the formation of a semisolid skin over the molten Al metal, which also hinders further oxidation [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations